The degree of organizational justice to the principals of public schools and their relationship to job satisfaction of teachers in public high schools in the districts of the northern West Bank - Shatha Lotfi Mahmoud Mohammad (My University, 2012)
This study aimed at identifying the level of the relationship between organizational justice and job satisfaction among secondary school teachers in government schools in the governorates of the Northern West Bank, and to clarify the effects of independent variables of(age, educational qualification, gender, years of experience, type of school, school location, and salary) on the teachers' perceptions and recognitions. The population of this study consisted of (12,388) teachers according to statistics of the Ministry of Education and Higher Education in Palestine (2010-2011). The researcher used the descriptive methods. The study was conducted on a sample of (555 teachers), represents (4.5%) of the population of the study, that has been selected by stratified random manner from the teachers of public secondary schools in the governorates of Northern West Bank. In order to achieve this study, the researcher prepared a questionnaire consisting of two sections containing (60) items. The first section to measure the issue of organizational justice distributed on three areas: ( Interactional Justice and relations within school, procedural justice, and distributive justice), while the second section to measure the issue of job satisfaction distributed on four areas: (promotion and rewards, tasks and duties, the relationship between the principals and teachers, and recognition and self respect) . The questionnaire was distributed randomly to the study sample in the educational directorates mentioned above. The researcher received (459)questionnaire (83%). To answer the questions and hypotheses, the researcher estimated the averages and percentages of each item and each area, and also of the whole instrument degree, She also used (One Sample T-test) and (T) test for groups (Independent T-test), and analysis of variance (ANOVA), (Scheffe - post hoc Test), and Pearson's correlation . This study showed the following results: - The degree of awareness of the practice of school principals to organizational justice in all domains (Interactional Justice and relations within school, procedural justice, and distributive justice)was very high. - The degree of awareness of the job satisfaction of public high schools teachers in the Governorates of the northern West Bank was very high in the domain (the relationship between teachers and the principal, and appreciation and self-esteem ) ,and for the domain (tasks and duties) was high ,but regarding the field of (promotion and rewards) was medium . The instrument degree as a whole was very high . - There is a strong positive correlation between the degree of organizational justice of public schools principals and job satisfaction for teachers of public secondary schools in the Governorates of the northern West Bank from their point of view, where the Pearson correlation coefficient (63.2%). - There were no significant mean differences at (α= 0.05) in the degree of the practice of school principals to organizational justice from point of view of teachers of public secondary schools in the Governorates of the northern West Bank due to the variable (age, academic qualification, years of experience, school site, salary). There were significant mean differences in the domains of (Interactional Justice and relations within school and distributive justice, total) according to gender, and the type of school, where the differences in favor of male teachers and boys' schools. - There were no significant mean differences at (α= 0.05) in the degree of the awareness of public secondary schools teachers in the Governorates of the northern West Bank to job satisfaction due to the age variable and the domains (promotion and rewards, the relationship between teachers and the principal, appreciation and self respect, and the whole domain). There were significant mean differences in the domain (tasks and duties) according to the qualification and the location of the school variables. In the light of these results, the researcher recommended the following: 1 - The attention of school principals to give teachers opportunities to participate more widely in the school business and strengthen the trust and respect for them. 2 - As much as possible, mitigation of the burden and paper work and programs that make teachers feel bored and limit the developing of their abilities and pertinence to their schools. 3 - Support of the Ministry of Education to the distinguished teachers providing material and moral incentives for them.

هدفت هذه الدراسة إلى تحديد درجة العدالة التنظيمية لدى مديري المدارس الثانوية وعلاقتها بالرضا الوظيفي لمعلمي المرحلة الثانوية في المدارس الحكومية في محافظات شمال الضفة الغربية، وبيان الاختلاف في استجابات المعلمين وفقاً للمتغيرات المستقلة:( العمر، والمؤهل العلمي، والجنس، وسنوات الخبرة، ونوع المدرسة، وموقع المدرسة، والراتب). وقد تكون مجتمع الدراسة من (12388) معلم ومعلمة وفق إحصائيات وزارة التربية والتعليم العالي الفلسطينية للعام (2010- 2011 ). وقد استخدمت الباحثة المنهج الوصفي، وتم اختيار عينة الدراسة بصورة العينة الطبقية العشوائية وحددت الباحثة المديريات التي شملتها الدراسة، بحيث أجريت الدراسة على معلمي ومعلمات المدارس الثانوية الحكومية في مديريات التربية والتعليم في شمال الضفة الغربية وكان عددهم ( 555) معلماً ومعلمة بنسبة 4.5% من مجتمع الدراسة. ومن أجل تحقيق أهداف هذه الدراسة أعدت الباحثة استبانة مكونة من قسمين تحتوي على (60 فقرة). القسم الأول يتناول موضوع العدالة التنظيمية موزع على ثلاثة مجالات : عدالة التعامل والعلاقات داخل المدرسة، وعدالة الإجراءات، وعدالة التوزيع، وأما القسم الثاني يتناول موضوع الرضا الوظيفي وهو موزع على أربع مجالات: مجال التعزيز والمكافآت، ومجال المهام والواجبات، ومجال العلاقة بين المدير والمعلمين، ومجال التقدير واحترام الذات. تم توزيع الاستبانة على عينة الدراسة وقد استرجعت الباحثة منها (459) استبانة أي ما نسبته (%83) من حجم العينة. وللإجابة عن أسئلة وفرضيات تم استخراج المتوسطات الحسابية والنسب المئوية لكل فقرة، ولكل مجال، وللدرجة الكلية للأداة، كما تم استخدام اختبار (One Sample T-test) واختبار (ت) للمجموعات المستقلةIndependent T- test) )، وتحليل التباين الأحادي( ANOVA )، واختبارات شفيه للمقارنات البعدية (Scheffe - post hoc Test)، ومعامل ارتباط بيرسون. أهم النتائج التي توصلت إليها الدراسة: - أن درجة ألعدالة التنظيمية لدي مديري المدارس الثانوية الحكومية كما براها المعلمون هي كبيرة جداً في المجال الكلي ومجالاتها الفرعية (عدالة التعامل والعلاقات داخل المدرسة، وعدالة الإجراءات، وعدالة التوزيع) . - أن درجة ألرضا الوظيفي لمعلمي ومعلمات المدارس الحكومية الثانوية في محافظات شمال الضفة الغربية هي كانت كبيرة جداً في المجال الكلي ومجالات(العلاقة بين المعلمين والمدير، التقدير واحترام الذات) وكانت كبيرة في مجال (المهام والواجبات) ، ومتوسطة في مجال(التعزيز والمكافآت). - توجد هناك علاقة ارتباطية ايجابية قوية بين درجة العدالة التنظيمية لدى مديري المدارس الحكومية وعلاقتها بالرضا الوظيفي لمعلمي المدارس الثانوية الحكومية في محافظات شمال الضفة الغربية من وجهة نظرهم ، حيث بلغ معامل ارتباط بيرسون (0.632). - لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α = 0.05) بين متوسطات استجابات معلمي المدارس الثانوية الحكومية في درجة ممارسة مديري المدارس الحكومية الثانوية للعدالة التنظيمية وفقاً للمتغيرات( العمر، المؤهل العلمي، سنوات الخبرة، موقع المدرسة، راتب المعلم) بينما كان هناك فروق في مجالات (عدالة التعامل والعلاقات داخل المدرسة، عدالة التوزيع، الكلي ) تبعا لمتغير الجنس ونوع المدرسة، حيث كانت الفروق لصالح المعلمين الذكور ومدارس الذكور. - لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α = 0.05) في متوسطات استجابات معلمي المدارس الثانوية الحكومية للرضا الوظيفي في محافظات شمال الضفة الغربية تعزى لمتغير العمر في مجالات (التعزيز والمكافآت، العلاقة بين المعلمين والمدير، التقدير واحترام الذات، والمجال الكلي) تبعاً لمتغير المؤهل العلمي وموقع المدرسة، والجنس، وسنوات الخبرة، ونوع المدرسة، ومجالات(التعزيز والمكافآت، العلاقة بين المعلمين والمدير، التقدير واحترام الذات) تبعاً لمتغير راتب المعلم ، بينما كان هناك فروق في مجال (المهام والوجبات) تبعاً لمتغير المؤهل العلمي، وموقع المدرسة . وفي ضوء نتائج الدراسة خرجت الباحثة بمجموعة من التوصيات منها: 1- الاهتمام من قبل مديري المدارس بإعطاء المعلمين فرص للمشاركة بصورة أوسع في الأعمال المدرسية وتعزيز الثقة والاحترام لديهم. 2- التخفيف قدر المستطاع من الأعباء والأعمال الورقية والبرامج الكثيرة التي تشعرهم بالملل وتحد من تطوير قدراته وانتمائهم لمدارسهم. 3- دعم وزارة التربية والتعليم للفئة المميزة من المعلمين وتقديم الحوافز المادية والمعنوية لهم.
درجة العدالة التنظيمية لدى مديري المدارس الحكومية وعلاقتها بالرضا الوظيفي لدى معلمي المدارس الثانوية الحكومية في محافظات شمال الضفة الغربية